Growth and diet of inanga (Galaxias maculatus) within a small New Zealand coastal pond system. Issue 1 (2nd January 2023) - Stuart, Rose E.; Ingram, Travis; Closs, Gerard P.
ABSTRACT: Inanga ( Galaxias maculatus ) are found in a range of freshwater habitats around much of the Southern Hemisphere. Although they are reasonably well studied within New Zealand, little is known about the populations found in coastal pond systems. This study focussed on inanga diet and population dynamics within a shallow pond complex in coastal Southland, investigating age, growth, distribution, and diet of juvenile inanga over a spring to autumn period. Otolith analysis indicated a three-month period (September to November) during which fish are hatching, with fish that hatched earlier growing more slowly than later fish. Inanga were found in only one location within the pond complex – a site featuring low water nutrient levels and less access by trout. Diet analysis showed high selectivity for chydorids and chironomid larvae, indicating a mixture of both benthic and pelagic foraging. Overall, this study has provided insight into inanga population dynamics in ponds, which have not previously been observed.